2018
DOI: 10.3382/ps/pey107
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental compression force and meat attribute changes in woody broiler breast fillets during short-term storage

Abstract: Woody breast (WB) is a myopathy of the Pectoralis major muscle in broilers that is characterized by increased hardness of the raw fillet. This defect increases economic losses due to associated decreased meat quality and the addition of training skilled laborers to identify problematic fillets. Therefore, the objectives of this study were to determine if compression force (CF) could be used as a non-invasive method of detecting WB and to assess changes in meat attributes during cold storage. Deboned fillets (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 17 publications
18
57
0
Order By: Relevance
“…(2017) found that WB scores increased as fillet weights increased regardless of the bird age. Chatterjee et al., 2016 , Livingston et al., 2019 , Mudalal et al., 2015 , and Sun et al. (2018) showed that the weights of normal fillets were consistently lower than those of fillets with the WB condition.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…(2017) found that WB scores increased as fillet weights increased regardless of the bird age. Chatterjee et al., 2016 , Livingston et al., 2019 , Mudalal et al., 2015 , and Sun et al. (2018) showed that the weights of normal fillets were consistently lower than those of fillets with the WB condition.…”
Section: Resultsmentioning
confidence: 92%
“… Dalgaard et al. (2018) and Sun et al. (2018) found that there was a significant difference in CF between WB and normal fillets.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…. Coon, Chen, and Owens (2018) found positive and significant correlations between compression force and the severity of WB condition (r = 0.79) in raw breast muscles, clearly incriminating the histological degeneration of muscle in its altered texture properties. Soglia et al (2017) reported that the enlargement of extracellular matrix and fibrosis might contribute in explaining the different texture properties between superficial and deep layers in WB samples, with the superficial part exhibiting a higher amount of larger particles and a higher compression force compared to deeper layers.…”
Section: Sensory Propertiesmentioning
confidence: 91%
“…The impact of the myopathies on the textural properties of chicken breast muscles has been profusely documented by studies applying both instrumental and sensory assessments. Sun, Koltes, Coon, Chen, and Owens () found positive and significant correlations between compression force and the severity of WB condition (r = 0.79) in raw breast muscles, clearly incriminating the histological degeneration of muscle in its altered texture properties. Soglia et al.…”
Section: Impact Of Wb Ws and Sm On Meat Qualitymentioning
confidence: 99%